Preparation method and application of turbine graphene for adsorption and removal of dye pollutants

The turbographene is prepared by modifying waste rubber tires with urea and using Joule hot flashing technology, which solves the problem of time-consuming, energy-consuming and poor adsorption effect of preparing carbon nanomaterials in the prior art, and achieves the effect of efficiently removing dye pollutants, and is environmentally friendly and free of secondary pollution.

CN118594481BActive Publication Date: 2025-04-04HEBEI UNIV OF TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202410730946.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-06-06
Publication Date
2025-04-04
Estimated Expiration
2044-06-06

AI Technical Summary

Technical Problem

In the prior art, when removing dye pollutants, the method of preparing carbon nanomaterials consumes time and energy, and has poor adsorption effect, long adsorption time, and there is a risk of secondary pollution in the environment.

Method used

Turbographene is prepared by using urea modified waste rubber tires through Joule hot flashing technology to remove dye contaminants as an adsorbent. The method includes dissolving, drying, roasting and flashing of waste rubber tires and urea particles in water to prepare turbine graphene with high specific surface area and porosity.

Benefits of technology

The adsorption amount and removal rate are significantly improved, close to 100%, and adsorption equilibrium can be achieved within 30 minutes. The adsorption mechanism is mainly pore filling and there is no risk of environmental secondary pollution.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118594481B_ABST
    Figure CN118594481B_ABST
Patent Text Reader

Abstract

The present invention provides a preparation method and application of turbine graphene for adsorbing and removing dye pollutants. Using waste rubber tires as raw materials, urea modification was used to prepare flash graphene (FGs) through flash Joule heating (FJH) technology, and batch adsorption experiments were carried out, which showed good results in adsorbing typical azo dyes (methyl orange and methylene blue). Compared with the material (BC) that has not been flash evaporated, the C element on the surface of FGs after ultra-high temperature flash evaporation is highly polymerized to form a layered turbine graphene structure, the number of micropores is increased, and the specific surface area is greatly increased. The removal rates of methyl orange and methylene blue increased from 8% to more than 90% and close to 100%, respectively, and the adsorption equilibrium was reached in 30 minutes. Compared with FGs that have not been modified with urea, FGs modified with urea have a higher content of turbine graphene and a better adsorption effect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of dye pollutant removal, and in particular to a preparation method and application of turbine graphene for adsorbing and removing dye pollutants. Background Art

[0002] The textile industry occupies an important position in China's manufacturing industry. China is a major textile and clothing manufacturer and exporter in the world. While the textile industry is booming, the water consumption and wastewater discharge of the textile industry are also increasing rapidly. Printing and dyeing wastewater is the main pollution generated by the textile industry. Printing and dyeing wastewater has the characteristics of large water volume, deep chroma, complex composition, and difficulty in degradation, which makes it very difficult to treat. Among them, azo dyes account for about 70% of the total dyes in the world. Methyl orange and methylene blue are common anionic and cationic azo dyes, which are widely used in papermaking, textiles, plastics, food, chemicals, cosmetics and other industries, so the pollution is also particularly serious.

[0003] Adsorption is considered to be a green and sustainable dye removal technology. Common adsorbents include biochar, molecular sieves, silica gel, activated alumina, zeolite, bentonite, etc. Among them, carbon nanomaterials (CNMs) including nano-biochar, carbon nanotubes, graphene, etc. are a type of adsorbent that has received widespread attention in recent years. Their main characteristics are large specific surface area, rich pores, and highly stable carbon structure, which can achieve carbon sequestration to a certain extent. However, the traditional method of preparing CNMs is generally time-consuming and energy-consuming, and often additional reagents are required to enhance the adsorption capacity, causing secondary environmental pollution, and the adsorption effect is poor and the adsorption time is long. Summary of the invention

[0004] In view of the deficiencies in the prior art, the technical problem to be solved by the present invention is to provide a preparation method and application of turbine graphene for adsorbing and removing dye pollutants.

[0005] The technical solution adopted by the present invention to solve the technical problem is:

[0006] In a first aspect, the present invention provides a method for preparing turbine graphene for adsorbing and removing dye pollutants, the preparation method comprising the following steps:

[0007] Step 1, dissolving and evenly stirring waste rubber tires with a particle size of no more than 150 μm and urea particles in water at a mass ratio of 0.5 to 2:1, and drying;

[0008] Step 2, roasting the material dried in step 1 for 1-3 hours in an inert gas atmosphere at a temperature of 400-800°C, and after roasting, cooling to room temperature for grinding and sieving for later use;

[0009] Step 3: Place the sample obtained in step 2 into a quartz tube or a ceramic tube for Joule flash treatment. The Joule flash treatment process is: set the initial voltage to 140-180V, the capacitance to 220-260mF, discharge the capacitor after charging, and pass the current through the sample to obtain flash turbine graphene.

[0010] Furthermore, the π–π* bond content in the flash turbine graphene is the percentage of π–π* bond energy to the total energy of C–C bonds, O–C–O bonds and π–π* bonds, which is 13-18%.

[0011] Furthermore, in step 1, the solid-liquid ratio is 1 g: 20-100 mL (deionized water), the drying temperature is 50-100° C., and the stirring time is 8-16 h.

[0012] Furthermore, in step 2, the mesh size of the sieve is consistent with the average particle size of the waste rubber tire raw material.

[0013] Furthermore, there is no calcite and magnesite in the flash turbine graphene, and the graphite (002) phase is dominant. Urea modification helps to increase the content of turbine graphene. The specific surface area of ​​flash turbine graphene is 20-50m 2 g -1 , the average pore size is 20-40nm.

[0014] Furthermore, the specific surface area of ​​flash turbine graphene is 30-45m 2 g -1 , the average pore size is 25-30nm.

[0015] In a second aspect, the present invention provides a method for removing dye pollutants, using the turbine graphene obtained by the preparation method for adsorption, the mass of the turbine graphene is 15-50 mg, and the pollutant concentration is 5-40 mg L -1 , add the turbo graphene to the pollutant, oscillate in a constant temperature oscillator at 25°C in the dark, the oscillation speed is 150-200rpm, and the adsorption time is not less than 10min.

[0016] Furthermore, the pollutants can achieve at least 80% removal rate within 15 min of adsorption time, and the equilibrium adsorption capacity is 15-30 mg g -1 .

[0017] Furthermore, the pollutant is an azo dye, and the azo dye is at least one of methyl orange or methylene blue, Congo red, and rhodamine B; the C element on the surface of the flash turbine graphene is highly polymerized to form a layered turbine graphene structure, the number of micropores is increased, and the specific surface area is greatly increased. Methyl orange and methylene blue are adsorbed by pore filling, and the adsorption removal rate reaches more than 90%, even close to 100%, and the adsorption equilibrium is reached within 30 minutes.

[0018] Compared with the prior art, the present invention has the following beneficial effects:

[0019] The present invention uses urea to modify waste tires, and prepares a turbographene by Joule thermal flash evaporation technology. The turbographene prepared by the method is used as an adsorbent to treat azo dye pollution in water bodies, which is a brand-new technical means. Its adsorption amount is significantly improved compared with the raw material without flash evaporation and the unmodified turbographene, and the removal rate is close to 100%. It can achieve adsorption equilibrium within 30 minutes, and the adsorption mechanism is mainly pore filling. The adsorbent prepared by the present invention and its application effect in dyes lay a practical and theoretical foundation for expanding the application of flash evaporation Joule heating FJH technology in environmental remediation.

[0020] In the present invention, the particles before flash evaporation are guaranteed to be within 100 meshes, which is beneficial to increasing the specific surface area of ​​the sample and reducing the pore size. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 Full XPS spectra of BC and FGs.

[0022] Figure 2 XPS C 1s spectra of BC and FGs.

[0023] Figure 3 FTIR spectra of BC and FGs.

[0024] Figure 4 Raman spectra of BC and FGs.

[0025] Figure 5 XRD spectra of BC and FGs, where *: quartz, ★: graphite (002), ●: silicon, SiC, Calcite, ◆: magnesite.

[0026] Figure 6 TEM images of CNMs.

[0027] Figure 7 Pore ​​size distribution (a) and nitrogen adsorption–desorption curves (b) of BC and N-CNM700.

[0028] Figure 8Removal efficiency of methyl orange by BC and FGs.

[0029] Fig. 9 Removal efficiency of methylene blue by BC and FGs.

[0030] Fig.10 Adsorption kinetics of methyl orange by BC and FGs.

[0031] Fig.11 Adsorption kinetics of methylene blue by BC and FGs. DETAILED DESCRIPTION

[0032] The present invention is further explained below in conjunction with the embodiments and drawings, but this is not intended to limit the scope of protection of the present application.

[0033] Embodiment 1:

[0034] The preparation method of turbine graphene for adsorbing and removing dye pollutants in this embodiment comprises the following steps:

[0035] Step 1: dissolve the waste rubber tires with a particle size of 100 mesh and urea granules in water at a mass ratio of 1:1, stir evenly, and dry; specifically: add the mixture of waste rubber tires and urea granules into a beaker at a solid-liquid ratio of 1g:20-100mL (deionized water), stir with a magnetic stirrer for 10 hours, and dry at 80°C.

[0036] Step 2, roasting the material dried in step 1 for 2 hours under a nitrogen atmosphere at a roasting temperature of 400-700°C, taking it out when the temperature drops to 100°C, cooling it to room temperature, grinding it, and sieving it for later use, with a 100-mesh sieve;

[0037] Step 3: Place the sample obtained in step 2 into a quartz tube for Joule flash treatment. The Joule flash treatment process is: set the initial voltage to 160V and the capacitance to 240mF. After charging is completed, the capacitor is discharged and the current passes through the sample to obtain flash turbine graphene.

[0038] In this embodiment, different calcination temperatures are set to 400, 550, and 700°C, and the obtained flash turbine graphene samples are uniformly named FGs. The samples at different calcination temperatures are respectively recorded as N-FG400, N-FG550, and N-FG700.

[0039] Comparative Example 1

[0040] In this comparative example, no urea granules are used, and only the waste rubber tires are subjected to Joule flash treatment. The specific process is:

[0041] Waste rubber tires (100 mesh) were placed in an oven and dried at 80°C, loaded into a crucible, compacted, and placed in a muffle furnace, ventilated with nitrogen, and heated at 10°C min-1 The temperature was raised to 400°C at a rate of 100°C and maintained for 2 h. When the temperature dropped to 100°C, the mixture was taken out and cooled to room temperature before grinding. After being sieved (100 mesh), the mixture was put into a sealed bag for later use and named BC.

[0042] The flash evaporation experiment was carried out using a Joule flash evaporation device, specifically including: accurately weighing 120 mg BC, placing the sample into a quartz tube with an inner diameter of 6 mm, with graphite blocks at both ends, and the copper sheet in close contact with the graphite block. The capacitor was then charged to reach a capacitance of 240 mF, with an initial voltage of 160 V. The charging was then stopped, the capacitor was discharged, and the current passed through the sample to obtain a flash product named FG.

[0043] The materials prepared above were subjected to the following relevant tests:

[0044] X-ray photoelectron spectroscopy: X-ray photoelectron spectroscopy (ESCALAB 250Xi, Thermofischer, USA) was used to analyze the changes in the surface elements and valence states of the materials, with a monochromatic aluminum x-ray source of 1486.6 eV for excitation.

[0045] Fourier transform infrared spectroscopy: Fourier transform infrared spectroscopy (Bruker, Germany, vertex 80V) was used to analyze the surface functional groups of CNMs.

[0046] Raman spectroscopy: Raman measurements of the materials were performed using a Raman spectrometer (LabRAM HR Evolution, Horiba, Japan) equipped with a 532 nm laser line to determine the chemical composition and structure.

[0047] X-ray diffraction: The FGs crystal structure was analyzed by X-ray diffraction (SmartLab SE, Rigaku, Japan), and Jade6.0 was used to identify the XRD features, bands, and spectral characteristics.

[0048] Transmission electron microscopy: The morphology of CNMs was observed by transmission electron microscopy (TECNAI G2 F20, FEI, USA). The specific surface area and pore size distribution of FGs were analyzed by fully automatic specific surface area and porosity analyzer (ASAP 2460, Micromeritics, USA).

[0049] Adsorption experiment: 40 mg of each material (BC, FG, N-FG400, N-FG550, N-FG700) was added to 40 mL of 20 mg L -1The centrifuge tube was placed in a contaminant centrifuge tube. The centrifuge tube was oscillated in a thermostatic oscillator (180 rpm) at 25°C in the dark. Sampling was performed every 10 minutes. Methyl orange sampling was stopped at 80 minutes, and methylene blue sampling was stopped at 90 minutes. After filtering with a 0.22 μm needle filter membrane, the concentrations of methyl orange and methylene blue were determined using a UV-visible spectrophotometer. Each sample was repeated three times.

[0050] Adsorption amount (q e ) and removal rate (R) are calculated as follows:

[0051]

[0052]

[0053] Where C0 and C e represent the initial concentration and equilibrium concentration, mg L -1 ; V is the volume of pollutant solution, in L; m is the mass of adsorbent, in g. The pseudo-first-order kinetic and pseudo-second-order kinetic models were used to fit the adsorption process.

[0054] Figure 1 The full XPS spectrum of the sample shows that the surface of BC includes C, N, O, S, Mg, Ca, Si and other elements, while after flash evaporation, there are almost no other elements on the surface of FGs except C and O. Although the flash evaporation process is very short, the ultra-high temperature (about 3000℃) makes N, S, Mg, Ca and other elements almost completely volatilize, leaving only C element, forming a highly carbon-polymerized material, and the presence of O element may be because the flash evaporation process does not isolate oxygen, so it remains.

[0055] Figure 2 The XPS C 1s spectrum of the sample shows that the C1s peak of BC can be divided into peaks at 284.4eV, 285.5eV, and 286.0eV, which are derived from C–C, C–H, and O–C–O bonds, respectively. The C1s peak of FGs can be divided into C–C, O–C–O, and π–π* bonds. The π–π* bond is a characteristic peak of graphene materials, which indicates that the flash evaporated FGs contain graphene components. The π–π* bond contents of FG and the three FGs are N-FG700 (16.39%) > N-FG550 (14.02%) > N-FG400 (13.89%) > FG (11.82%), where the π–π* bond content is the percentage of the π–π* bond energy to the total energy of the C–C bond, O–C–O bond and π–π* bond, indicating that urea modification treatment increases the graphene content in the sample, and the higher the calcination temperature, the higher the graphene content, but the temperature cannot be infinitely high. When it reaches about 800°C, the π–π* bond content can still be guaranteed to be about 15%.

[0056] Figure 3 is the FTIR spectrum of the sample, from Figure 3 As can be seen, BC without flash distillation contains abundant functional groups, including 2920 cm -1 Nearby C–H stretching, 1600–1450 cm -1 Aromatic C=C bond, 1010cm -1 nearby C–O bonds, and 900–650 cm -1 Aromatic C–H stretching at .

[0057] After flash evaporation, the entire wavelength range (4000–400cm -1 ) All peaks are greatly weakened, with only the peaks at 1750–1540 cm -1 and 1200–1000 cm -1 There are some oxygen-containing functional groups C=O and C–O, and few aromatic functional groups. This indicates that during the flash evaporation process, the carbon chains of the originally relatively stable aromatic functional groups are broken under the impact of high temperature, and some C combines with O in the air to form oxygen-containing functional groups, while more C may form graphitized structures during the flash evaporation process, resulting in the loss of functional groups.

[0058] Figure 4 The Raman spectrum of BC shows D (1350cm -1 ) and G(1582cm -1 ) represent the defects of carbon atom lattice and the in-plane stretching vibration of sp2 hybridized carbon atoms respectively.

[0059] The Raman spectra of the flash products all show three typical characteristic peaks, namely D peak, G peak and 2D peak (2700 cm -1 ). D / I G It represents the intensity ratio of D peak and G peak, which can be used to compare the graphitization degree or defect degree of carbon materials. D / I G From large to small, they are N-FG550 (0.479) > FG (0.402) > N-FG700 (0.367) > N-FG400 (0.212), all of which are smaller than BC (0.844), and are much smaller than other carbon nanomaterials in general. At the same time, the value is less than 1, indicating that the sample contains graphene structure and the degree of disorder is relatively small. The 2D peak is a double phonon resonance second-order Raman peak, which is used to characterize the interlayer stacking mode of carbon atoms in graphene samples. 2D / I G The larger the ratio, the fewer the number of graphene layers. 2D / IG From large to small, they are N-FG550(0.801)>FG(0.776)>N-FG700(0.717)>N-FG400(0.712).

[0060] Figure 5 is the XRD pattern of the sample, Figure 5 It can be seen that BC mainly contains quartz (SiO2), magnesite (MgCO3) and calcite compounds (CaCO3), which are similar to the composition of most biochar materials. The XRD spectra of the four flash products show completely different crystal phases. FGs all contain obvious graphite (002) crystal plane diffraction peaks (2θ=26.28°), indicating that FGs have a high degree of graphitization and good crystallinity. The graphite (002) characteristic peak of FGs is asymmetric, and the tail presents a small angle, which is the vortex characteristic of flash graphene, indicating that turbine graphene (tFG) is generated. In addition, the graphite (002) characteristic peaks in N-FG400, N-FG550 and N-FG700 modified with urea are significantly higher than those in unmodified FG, which also shows that urea modification is beneficial to increase the graphene content.

[0061] Figure 6 Figure 1 is a TEM image of FGs, and its morphological structure is observed through TEM images. As can be seen from the figure, the main form of the material is well-dispersed nanosheets, indicating that in the rapid flash process, large black carbon particles are impacted by high temperature to form small-sized carbon nanomaterials, and the size of the nanosheets shows the rule of FG>N-FG400>N-FG550>N-FG700. The turbine graphene (tFG) formed by flash evaporation originates from the mobile carbon of the precursor carbon source. With the generation of mobile carbon, multi-faceted nanoparticles begin to nucleate, and then these nanoparticles gradually merge, and finally form multi-faceted sheet-like tFG along the top of the nucleated particles. Most of the FGs shown in the TEM images of FG, N-FG400 and N-FG550 show a nanosheet structure, which corresponds to the nanoparticle nucleation stage in the tFG formation process. In the TEM image of N-FG700, its thickness is thin, the particles are gradually connected, and the tFG morphology has initially appeared. This result shows that in the FJH process, in addition to equipment parameters such as resistance and voltage, the properties of the precursor itself for flash Joule heating are also very important for the formation of flash graphene. In order to increase the turbine graphene content of the product, the pretreatment pyrolysis temperature should be increased as much as possible. At the same time, urea modification is an effective method to increase the turbine graphene content.

[0062] Figure 7 The pore size distribution (a) and nitrogen adsorption-desorption curve (b) of BC and N-FG700 are compared with the specific surface area and pore structure of BC and N-FG700. It can be seen from the figure that N-FG700 (40.387m2 g -1 ) has a significantly larger specific surface area than BC (9.505m 2 g -1 ), which is mainly due to the generation of more micropores ( Figure 7 (a) and Table 1), which also makes the average pore size of N-FG700 (25.773 nm) significantly smaller than that of BC (49.972 nm).

[0063] According to the classification of IUPAC adsorption isotherms, BC and FGs in the present invention belong to type IV adsorption-desorption isotherms ( Figure 7 b), which is the H3 hysteresis loop, usually seen in layered aggregates, produces slit-like holes, which further confirms the generation of flake graphene. Although BC and FGs are both layered structures, it can be seen from the previous analysis that FGs contain turbographene components, whose most important feature is rotational stacking rather than AB stacking, so it is easy to be peeled off. BC has not undergone the ultra-high temperature flash evaporation process, and its main form may be a tight layered structure.

[0064] Table 1 Specific surface area and pore size analysis of BC and N-FG700

[0065]

[0066] Figure 8 This is a comparison of the removal rates of methyl orange by BC and FGs. Figure 8 It can be seen that compared with BC (R=8%), the adsorption effect of FGs on methyl orange after flash evaporation was significantly enhanced, among which the removal rate of urea-modified FGs (R greater than 90%) was significantly better than that of unmodified FG (R=71%) (P<0.05).

[0067] Fig. 9 This is a comparison chart of the removal effects of BC and FGs on methylene blue. For the adsorption of methylene blue, the removal efficiency of urea-modified FGs is improved compared to that of unmodified FG, approaching 100%, but it is significantly improved compared to BC, with the removal rate increasing from 8% to nearly 100%.

[0068] Fig.10 and Fig.11 The adsorption kinetics of BC and FGs to methyl orange and methylene blue are shown in Figure 2. Fig.10 and Fig.11 It can be seen that the adsorption of methyl orange and methylene blue by FGs is very rapid, and the adsorption equilibrium is completely reached in less than 1 h, and the adsorption amount is relatively high.

[0069] In order to further clarify the dominant mechanism of adsorption, the kinetic model was used to fit the adsorption process. Both pseudo-first-order kinetics and pseudo-second-order kinetics can well fit the adsorption process of methyl orange and methylene blue by four FGs (R 2 >0.98) (Tables 2 and 3), indicating that the adsorption process includes both physical adsorption and chemical adsorption.

[0070] In the FTIR analysis, it can be seen that due to the formation of graphitized carbon structure, FGs are unlikely to adsorb pollutants through complexation or hydrogen bonding of functional groups, and chemical adsorption may not be the main mechanism of the process. The data of pseudo-first-order kinetics and pseudo-second-order kinetics fitting show that the equilibrium adsorption amount of methyl orange and methylene blue by urea-modified N-FG400, N-FG550, and N-FG700 is q e1 and q e2 The results are consistent with the trend of π-π* bond content in XPS analysis. Therefore, the key role of FGs in the adsorption of methyl orange and methylene blue may be related to the graphene structure.

[0071] Table 2 Methyl orange adsorption parameters

[0072]

[0073] Table 3 Methylene blue adsorption parameters

[0074]

[0075] The adsorption mechanism of carbon materials for azo dyes mainly includes electrostatic adsorption, pore filling, hydrogen bonding, π-π interaction, proton migration, chemical precipitation and hydrophobic interaction. In the present invention, due to the lack of functional groups on the surface of FGs, chemical adsorption related to functional groups may not play a dominant role. From the pore analysis, it can be seen that the micropores of FGs are significantly higher than those of BC, which allows pollutants to be adsorbed by the physical method of pore filling. At the same time, the turbine graphene component of FGs has been shown to exist in a rotationally stacked manner. A large number of such structures help to reduce interlayer coupling, increase the plane spacing, and make it easier to peel off into a single layer of graphene. After peeling, the layers are not easy to couple again, so the dispersion effect in aqueous solution is excellent, which also enables it to more fully combine with pollutants, thereby improving the adsorption performance of FGs.

[0076] Compared with other adsorbents (Table 4), the adsorption performance (adsorption amount or adsorption equilibrium time) of FGs showed better performance, and it was able to achieve the maximum equilibrium adsorption amount in the shortest adsorption equilibrium time.

[0077] Table 4 Comparison of performance of turbine graphene (N-FG700) and other adsorbents

[0078]

[0079] In addition, the experiment shows that under the same adsorption test conditions, the adsorption capacity of methyl orange without urea modification is only 13 mg g -1 The removal rate is low, and the adsorption amount of flash turbine graphene obtained at different calcination temperatures is slightly different, but as a whole, it can ensure a high removal rate (about 90% or more) within a very short adsorption time (within 30 minutes), and the adsorption amount is higher.

[0080] Any matters not described in the present invention are applicable to the prior art.

Claims

1. A method for preparing turbine graphene for adsorbing and removing dye pollutants, characterized in that: The preparation method comprises the following steps: Step 1, dissolving and evenly stirring waste rubber tires with a particle size of no more than 150 μm and urea particles in water at a mass ratio of 0.5 to 2:1, and drying; Step 2, roasting the material dried in step 1 for 1-3 hours in an inert gas atmosphere at a temperature of 400-800°C, and after roasting, cooling to room temperature for grinding and sieving for later use; Step 3, placing the sample obtained in step 2 into a quartz tube or a ceramic tube for Joule flash treatment, wherein the Joule flash treatment process is as follows: setting the initial voltage to 140-180V, the capacitance to 220-260mF, discharging the capacitor after charging, and passing the current through the sample to obtain flash turbine graphene; After flash evaporation, there are almost no other elements on the surface of FGs except C and O. Urea is used to increase the content of graphene in the sample. The π–π* bond content in flash turbine graphene is the percentage of π–π* bond energy to the total energy of C–C bonds, O–C–O bonds, and π–π* bonds, which is 13-18%; The C element on the surface of the flash turbine graphene is highly polymerized to form a layered turbine graphene structure, the number of micropores is increased, and the specific surface area is greatly increased. Methyl orange and methylene blue are adsorbed by pore filling, and the adsorption removal rate reaches more than 90%, and the adsorption equilibrium is reached within 30 minutes.

2. The preparation method according to claim 1, characterized in that: In step 1, the solid-liquid ratio is 1 g: 20-100 mL of deionized water, the drying temperature is 50-100° C., and the stirring time is 8-16 h.

3. The preparation method according to claim 1, characterized in that: In step 2, the mesh size of the sieve is consistent with the average particle size of the waste rubber tire raw material.

4. The preparation method according to claim 1, characterized in that: There is no calcite and magnesite in the flash turbine graphene, and the graphite (002) phase is the main phase. Urea modification helps to increase the content of turbine graphene. The specific surface area of ​​flash turbine graphene is 20-50m 2 g -1 , the average pore size is 20-40nm.

5. The preparation method according to claim 1, characterized in that: The specific surface area of ​​flash turbine graphene is 30-45m 2 g -1 , the average pore size is 25-30nm.

6. A method for removing dye contaminants, characterized in that: The turbine graphene obtained by any preparation method according to claim 1-5 is used for adsorption, the mass of the turbine graphene is 15-50 mg, and the pollutant concentration is 5-40 mg L -1 , add the turbo graphene to the pollutant, oscillate in a constant temperature oscillator at 25°C in the dark, the oscillation speed is 150-200rpm, and the adsorption time is not less than 10min.

7. The removal method according to claim 6, characterized in that: The pollutants can be removed by at least 80% within 15 minutes of adsorption, and the equilibrium adsorption capacity is 15-30 mg g -1 .

8. The removal method according to claim 6, characterized in that: The pollutant is an azo dye, and the azo dye is at least one of methyl orange or methylene blue, Congo red, and rhodamine B.